Assess the nutritional value of faba bean (Vicia faba) and peas (Pisum sativum) residue in nylon bags (In Sacco) (Latakia University Journal -Biological Sciences Series, 2019)
This study was conducted to determine the chemical composition of the residues resulting from faba bean and peas (Larache - pods peel) as well as the digestion of dry matter, crude protein, and crude fiber for these wastes in nylon bags (IN SACCO) and to demonstrate the possibility of using these residues in ruminants feeding. The results showed that the chemical composition of these residues is almost identical in terms of the proportion of each of the dry matter, organic matter and ash. In terms of crude protein, faba bean residue (Larache - pods peel) has surpassed 8.69%, 7.33% respectively on the remnants of peas 6.25%, 6.06%, respectively, and significant differences at (P